Evidence for the southernmost pre-industrial human expansion on Isla Hornos (Isla Lokoshpi), Chile - Buma, Brian; Morello Repetto, Flavia; Rodriguez, Karina; Fillol, Alberto Serrano (My University, 2022)
The authors provide an initial report on possibly the southernmost expansion of humans in pre-industrial times. The archaeological site, in the Cape Horn archipelago, consists of a campfire site, fragments of a weapon, and butchered bones. Radiocarbon dating places the site c. 260-460 years BP.
Keywords: chile; isla hornos; human expansion; archaeology; tree line; biogeography